Forage accumulation and nutritive value of four peanut (Arachis hypogaea L.) market types in the US Southern Great Plains - Travis Witt; Brian Northup; Manisha Ojha; Naveen Puppala (Legume Science, 2023)
Abstract Dual use crops are becoming popular as resources like land and water become scarcer. Annual peanuts are an important food crop grown worldwide that can also be used as forage or hay. Replicated trials evaluated the late season (≥15 weeks after planting) forage accumulations and nutritive values (acid detergent fiber, carbon content, crude protein, invitro true digestibility, neutral detergent fiber, nitrogen content, and relative feed value) of four market types near Clovis, NM and El Reno, OK in 2019 and 2020. Statistical analyses (p ≤ .05) showed all traits were affected by the interaction between market type and growing environment. Overall, forage accumulations for all market types ranged from 2.7 to 6.5 Mg ha−1 with relative feed values of 107–155. The location average across sites was 4.45 Mg ha−1 with relative feed value of 132. The Virginia market types produced large amounts of biomass. However, the Valencia market type generated the greatest nutritive values. This study indicates harvesting late‐season biomass of peanuts for hay may be an option that allows producers to generate more income from limited land and water resources. However, both market type and environmental factors, such as rainfall/irrigation, play important roles in production and forage nutritive values of peanut forage.